PENGARUH VARIASI SUDUT SERANG SUDU PADA PRESTASI TURBIN ANGIN - Sulistyo Atmadi; Ahmad Jamaludin Fitroh; Firman Hartono (Jurnal Teknologi Dirgantara, 2006)
Research on variations of angle of attack turbine blade has been conducted to investigate their correlation with windturbine performances, and for these purposes, AEROFOIL LS (1)-0417 MOD has been selected with 4 angle variations. The first variation is selscted with constant slipstream, the second with Cl max of 0.3, while the third and fouth variations with Cl max of 0.5 and 0.7 respectively. Based on blade element and momentum theory for obtaining efficiency, the following results for all the four variations are 18.15 percent, 16.46 percent, 16.15 percent and 16.26 percent. Hence, it can be concluded that, a highest efficiency is obtained with a constant slipstream as in case 1. In practice, to achieve such configuration, a more accurate blade fabricantion process is required to obtain the highest efficiency. Keywords: Sudu, Sudut serang.